Safety of guselkumab with and without prior TNF-α inhibitor treatment: pooled results across four studies in patients with psoriatic arthritis - Rahman, P; Boehncke, W-H; Mease, PJ; Gottlieb, AB; McInnes, IB; Shawi, M; Wang, Y; Sheng, S; Kollmeier, AP; Theander, E; Yu, J; Leibowitz, E; et al. (Journal of Rheumatology, 2023)
Objective: Assess pooled safety results through the end of the Phase 2/3 studies of guselkumab (≤2 years) in tumor necrosis factor-α inhibitor (TNFi) -naïve and -experienced patients with psoriatic arthritis (PsA).